Necrotizing Soft Tissue Infections, the Challenge Remains - Nawijn, Femke; Hietbrink, Falco; Peitzman, Andrew B.; Leenen, Luke P. H. (Frontiers in Surgery, 2021)
Background: Necrotizing Soft Tissue Infections (NSTIs) are uncommon rapidly spreading infection of the soft tissues for which prompt surgical treatment is vital for survival. Currently, even with sufficient awareness and facilities available, ambiguous symptoms frequently result in treatment delay. Objective: To illustrate the heterogeneity in presentation of NSTIs and the pitfalls entailing from this heterogeneity. Discussion: NSTI symptoms appear on a spectrum with on one side the typical critically ill patient with fast onset and progression of symptoms combined with severe systemic toxicity resulting in severe physical derangement and sepsis. In these cases, the suspicion of a NSTI rises quickly. On the other far side of the spectrum is the less evident type of presentation of the patient with gradual but slow progression of non-specific symptoms over the past couple of days without clear signs of sepsis initially. This side of the spectrum is under represented in current literature and some physicians involved in the care for NSTI patients are still unaware of this heterogeneity in presentation. Conclusion: The presentation of a critically ill patient with evident pain out of proportion, erythema, necrotic skin and bullae is the classical presentation of NSTIs. On the other hand, nonspecific symptoms without systemic toxicity at presentation frequently result in a battery of diagnostics tests and imaging before the treatment strategy is determined. This may result in a delay in presentation, delay in diagnosis and delay in definitive treatment. This failure to perform an adequate exploration expeditiously can result in a preventable mortality.